2020
DOI: 10.1007/s00402-020-03421-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancellous allogenic and autologous bone grafting ensure comparable tunnel filling results in two-staged revision ACL surgery

Abstract: Objectives Patients with recurrent instability after anterior cruciate ligament (ACL) reconstruction often present with enlarged or misplaced tunnels and bone grafting is required prior to the actual revision reconstruction. Autologous bone grafting features limited quantity and donor site morbidity. These problems may be eliminated utilizing cancellous bone allografts, but their efficiency and reliability have not been investigated systematically. The aim of the present study was to compare tunnel filling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Therefore, when performing ACL repair using the DIS technique the distance between the cylindrical implant site and the tibial joint line is decisive in the revision surgery setting: If a distance of 20 mm or more is left between the monobloc and the tibial joint line, an anatomic bone tunnel can be created in revision ACL-R without concerns regarding confluent tibial tunnels or a lack of bone stock for graft fixation in the subchondral portion of the tunnel. If the distance between the DIS implant and the joint line is lower than 20 mm, a two-stage revision surgery with bone grafting of the defect should be considered, corresponding to the established procedure in revision ACL-R in case of recurrent instability after previous ACL-R [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, when performing ACL repair using the DIS technique the distance between the cylindrical implant site and the tibial joint line is decisive in the revision surgery setting: If a distance of 20 mm or more is left between the monobloc and the tibial joint line, an anatomic bone tunnel can be created in revision ACL-R without concerns regarding confluent tibial tunnels or a lack of bone stock for graft fixation in the subchondral portion of the tunnel. If the distance between the DIS implant and the joint line is lower than 20 mm, a two-stage revision surgery with bone grafting of the defect should be considered, corresponding to the established procedure in revision ACL-R in case of recurrent instability after previous ACL-R [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of recurrent ACL instability is a challenging procedure: the history of previous ACL reconstruction (ACL-R) including a previously harvested tendon as well as the position of an eventual widened bony tunnel can compromise the graft fixation [11][12][13]. In both primary and revision ACL-R, the majority of orthopedic surgeons' rely on a hybrid fixation of the ACL graft at the tibial side.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancellous bone allograft has been described in a wide range of settings and has been recently used for patients with recurrent instability after anterior cruciate ligament (ACL) reconstruction (Kodach et al 2008). A recent study by Prall et al investigated the use of PAA treated freeze-dried cancellous bone chips and compared its use with autologous cancellous bone grafting (Prall et al 2020). In the study, it is reported that cancellous bone allograft was used for filling of enlarged or misplaced tunnels in two-staged revision ACL surgery.…”
Section: Cancellous Bone Use In Tunnel Fillingmentioning
confidence: 99%
“…Für eine erneute VKB Plastik ist es je nach Weitung und Lage der Bohrkanäle in einigen Fällen notwendig diese in einer ersten OP mit Knochenmaterial aus dem Beckenkamm aufzufüllen. Erst nach 4–6 Monaten kann dann die wiederholte VKB-Rekonstruktion mit einem neuen Transplantat erfolgen 14 , 24 , 35 . Der lange Rehabilitationszeitraum ist bei Patient*innen mit einer großen psychischen Belastung verbunden.…”
unclassified